Implementasi Model Pembelajaran Inovatif Kurikulum Merdeka Bagi Siswa SMP Negeri 2 Kanatang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The Independent Curriculum demands a paradigm shift in learning from teacher-centered to student-centered learning through the implementation of innovative learning models. However, the implementation of the Independent Curriculum at SMP Negeri 2 Kanatang still faces various obstacles, especially the limited understanding of teachers in implementing innovative learning models. Therefore, this community service activity aims to improve teachers' understanding and skills in implementing innovative learning models in accordance with the principles of the Independent Curriculum. The method of implementing activities uses a combination of lectures, discussions, and direct practice which begins with observation and interviews, followed by planning, implementation of socialization, and evaluation. The subject of the activity was 20 teachers of SMP Negeri 2 Kanatang from various subjects. The results of the activity showed that teachers responded very positively to the implementation of innovative learning models. The results of the questionnaire showed a percentage of 100% in the aspect of learning planning, impact on students, as well as satisfaction and expectations, while in the aspect of learning implementation, 67% agreed and 33% were neutral. These findings show that this activity is effective in improving teacher understanding, although further assistance is still needed to optimize implementation in the classroom. Overall, this activity is considered successful and feasible to continue as an effort to improve the quality of learning and the implementation of the Independent Curriculum in a sustainable manner at SMP Negeri 2 Kanatang.